If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6 + 6x = 69 Reorder the terms: 6 + 3x + 6x = 69 Combine like terms: 3x + 6x = 9x 6 + 9x = 69 Solving 6 + 9x = 69 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 9x = 69 + -6 Combine like terms: 6 + -6 = 0 0 + 9x = 69 + -6 9x = 69 + -6 Combine like terms: 69 + -6 = 63 9x = 63 Divide each side by '9'. x = 7 Simplifying x = 7
| x+(x+7)+x+(x-7)= | | 14k+-8+9=-13 | | (2x+2)30=(2x+4)27 | | 9x+4-2x=3(x+8) | | 2-3x=38 | | 3y*9y^2= | | (10+3+2x)10=(9+3x)9 | | 11x-104=2x-5 | | 4x-3+5x=25 | | 20*8x+0.2*1000=40*8x | | 0=x^2+8x+14 | | (3x-35)+(5x-25)=180 | | 124=6x+d | | 2(x-4)=x+-12+2x | | 124=6x+4 | | 0=-16t^2+380 | | -2y+1=17 | | xy*3x= | | (X+3)6=(x+1)7 | | 8p*2p-7=32 | | y=-16t^2+380 | | 33x+x^2-370=0 | | 13-3x=4(y-2) | | (9+x)9=15(15) | | r*(7+10)=24 | | 5y-2-[6-(3-y)]=4(y-3)+7 | | 18x=9(20) | | (8+2+x)8=(9+x-1)9 | | 5p*3=10 | | 9+7x+x=38 | | 8-3(p-5)=2x+6 | | 55=10+5ln(3x+1) |